Electrical resistivity evolution in electrodeposited Ru and Ru-Co nanowires. (10th April 2022) - Moon, Jun Hwan; Kim, Seunghyun; Kim, Taesoon; Jeon, Yoo Sang; Kim, Yanghee; Ahn, Jae-Pyoung; Kim, Young Keun
Highlights: Propose a strategy to reduce electrical resistivity and complexity of current interconnect structure in ICs. Emulate a semiconductor metallization environment employing porous nano-templates. Design nanoscale Ru and Ru-Co structures by electrodeposition. Uncover electrical properties of Ru-based nanowires and microstructural evolution. Abstract: Nanoscale ruthenium (Ru)-based materials are promising replacements for existing multilayered Cu interconnects in integrated circuits. However, it is not easy to apply the results of previously reported studies directly to the electrochemical damascene process because the previous studies have mainly focused on thin films by dry deposition. Here, we report the electrical resistivity and microstructure of electrodeposited Ru nanowires. We estimate that the resistivity value of a 10 nm diameter Ru nanowire to be 71.6 μΩ cm after analyzing the resistivity values of individual nanowires with various diameters. Furthermore, we investigate the electrical properties of Ru x Co1- x nanowires where x is 0.04–0.99 at.% as possible replacements of the current TaN barrier structures. Over the entire composition range, the resistivity values of alloys are much lower than that of the conventional TaN. Additionally, Ru and Ru-alloy nanowires surrounded by dielectric silica are thermally stable after 450 °C heat treatment. Therefore, the nanoscale Ru and Ru-Co alloys possessing low resistivity values can be candidates for the interconnect and barrier materials, respectively.